Progression of Blood Flow Restricted Resistance Training in Older Adults at Risk of Mobility Limitations - Cook, Summer B.; Cleary, Christopher J. (Frontiers in Physiology, 2019)
Blood flow restriction (BFR) resistance training leads to increased muscle mass and strength but the progression leading to adaptations may be different as strength gains are often to a lesser magnitude than high-load (HL) training. The impact of training loads and repetitions on older adults’ muscle mass and strength following BFR or HL training was evaluated. Twenty-one older adults (67-90 years) classified as being at risk of mobility limitations were randomly assigned to HL (n=11) or BFR (n=10) knee extension (KE) and flexion (KF) training twice per week for 12 weeks. Strength was measured with 10-repetition maximum (10-RM) tests and isometric contractions. Cross-sectional area (CSA) of the quadriceps and hamstrings was measured. HL and BFR interventions increased 10-RM KF and isometric strength (P<.05) and hamstrings CSA increased an average of 4.8+5.9% after HL and BFR training (time main effect P<.01). There were no differences between the training groups (time x group interactions P>.05). The rate of progression of KF training load and repetitions was comparable (time x group interactions of each variable P>.05). The groups averaged an increase of .50+.25 kg∙week-1 and 1.8+.1.7 repetitions∙week1 of training (time main effects P<.05). The HL training group experienced greater improvements in KE 1-RM strength than the BFR group (60.7+36.0% vs 35.3+25.5%; P=.03). In both groups, isometric KE strength increased 17.3+18.5% (P=.001) and there were no differences between groups (P=.24). Quadriceps CSA increased (time main effect P<.01) and to similar magnitudes (time x group interaction P=.62) following HL (6.5+3.1%) and BFR training (7.8+8.2%). The HL group experienced accelerated progression of load when compared to BFR (.90+.60 kg∙week-1 vs .30+.21 kg∙week-1; P=.006) but was not different when expressed in relative terms. BFR training progressed at a rate of 2.2+.43 repetitions∙week-1 while the HL group progressed at 3.6+1.3 repetitions∙week-1 (P=.003). HL training led to greater increases in KE 10-RM and it may be attributed to the greater load and/or faster rate of progression of the load throughout the 12-week training period and the specificity of the testing modality. Incorporating systematic load progression throughout BFR training periods should be employed to lead to maximal strength gains.